A proteção jurídica relacionada às pessoas neurodivergentes dentro do Estado Democrático de Direito - ASATO, Sofia M. R.; DURAN, Camila M. A.; LIMA, Amanda N.; LIMA, Laura N.; SILVA, Flávia C.; SUNAKOZAWA, Lúcio F. (ANAIS DO ENIC, 2024)
-